Oxymoron as a leading means of creating the artistic world of Francois Vion's poetry (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article contains the analysis of the functioning oxymoronic designs in poetically system lyrics of Francois Viion. The author attempts to study antinomic nature and specifics of the creation of the original semantic qualities through the use of an oxymoron in the poetic tradition of the late middle Ages. It is revealed that the art world F. Viion, in large measure, is based on the principle of ironic game, the destruction rules and regulations courtly letters, «semantic impertinence».
Keywords: oxymoron; Francois Viion; poetry; nonsense; ballad